2020
DOI: 10.1021/acs.jnatprod.0c00650
|View full text |Cite
|
Sign up to set email alerts
|

Eleutheroside E Enhances the Long-Term Memory of Radiation-Damaged C. elegans through G-Protein-Coupled Receptor and Neuropeptide Signaling Pathways

Abstract: Eleutheroside E (EE), a principal active compound of Acanthopanax senticosus, has been shown to have a certain neuromodulation effect. Our previous study indicates that EE protects nerve damage caused by radiation. However, its specific function and underlying mechanism remain unknown. Therefore, the objective of this study is to apply the C. elegans model to illuminate the property and mechanism of EE protecting against nerve damage caused by radiation. Here, we found that EE significantly improved the long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Fatty acid metabolism usually takes place in the intestine. It has been reported that EE mainly plays a role in the nervous system 13,27 . Therefore, we speculated that EE might play a lipid‐lowering effect through brain–gut communication.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Fatty acid metabolism usually takes place in the intestine. It has been reported that EE mainly plays a role in the nervous system 13,27 . Therefore, we speculated that EE might play a lipid‐lowering effect through brain–gut communication.…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that EE mainly plays a role in the nervous system. 13,27 Therefore, we speculated that EE might play a lipid-lowering effect through brain-gut communication. In C. elegans, the loss of unc-13 will inhibit the release of typical neurotransmitters in transparent synaptic vesicles, 28 while the loss of unc-31 will inhibit the release of biogenic amines and neuropeptides in dense synaptic vesicles.…”
Section: Ee Significantly Regulated Genes and Metabolites Related To ...mentioning
confidence: 99%
“…The results showed that EE significantly protected C. elegans against the damage caused by gamma irradiation. They also showed that the long-term memory of the C. elegans induced by gamma irradiation was improved after treatment with EE [96]. Ceramide's effects on the irradiated germ cells of C. elegans have been investigated by Yang et al [84].…”
Section: Dietary or Pharmacological Interventions To Reduce Effects Of Radiationmentioning
confidence: 98%
“…Recently, certain phytochemical components have been used to improve C. elegans' resistance against ionizing irradiation. The protective effects of Eleutheroside E (EE) against gamma irradiation have been studied by Liu et al [96]. Eleutheroside E is a compound form Acanthopanax senticosus, which is a native plant of East Asia, found in China and Japan.…”
Section: Dietary or Pharmacological Interventions To Reduce Effects Of Radiationmentioning
confidence: 99%
“…1 ). Eleutheroside E also has extensive pharmacological activities, including anti-lipogenesis [32] , treatment of diabetic nephropathy [33] , treatment of rheumatoid arthritis [34] , treatment of postmenopausal osteoporosis [35] , neuroprotection [36] , [37] and anti-ischemia–reperfusion injury [38] . In recent years, with the continuous expansion and deepening of research on the action mechanism of eleutheroside B and eleutheroside E, extracts with eleutheroside B and eleutheroside E as index components have been favored by China, Japan, South Korea, and Southeast Asian countries.…”
Section: Introductionmentioning
confidence: 99%